On $\tilde{g} (1,2)^\star$-closed Sets - O. Ravi; R. Bhavani; S. Murugesan; I. Rajasekaran (International Journal of Mathematics And its Applications, 2015)
In this present paper, we introduce a new class of sets namely $\tilde{g} (1,2)^\star$-closed sets in bitopological spaces. The notion of $\tilde{g} (1,2)^\star$-interior is defined and some of its basic properties are studied. Also we introduce the concept of $\tilde{g} (1,2)^\star$-closure in bitopological spaces using the notion of $\tilde{g} (1,2)^\star$-closed sets.